2016
DOI: 10.1007/s00221-016-4751-0
|View full text |Cite
|
Sign up to set email alerts
|

Implicit motor sequence learning in schizophrenia and in old age: reduced performance only in the third session

Abstract: Although there still is conflicting evidence whether schizophrenia is a neurodegenerative disease, cognitive changes in schizophrenia resemble those observed during normal aging. In contrast to extensively demonstrated deficits in explicit learning, it remains unclear whether implicit sequence learning is impaired in schizophrenia and normal aging. Implicit sequence learning was investigated using a computerized drawing task, the 'implicit pattern learning task (IPLT)' in 30 stable patients with schizophrenia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This could indicate that motor memories are either robust, less susceptible to interference or more efficiently retrieved in our old participants (Brashers-Krug et al, 1996). Nevertheless, the improved consolidation we observed in the old group was unexpected because studies generally report either reduced (relative to young subjects) or complete absence of performance improvement during retesting of motor sequence tasks in older adults (Brown et al, 2009;King et al, 2013;Cornelis et al, 2016;Meissner et al, 2016). Late improvement (after 12 or 24-h off-line period) of GMS was also reported in elderly individuals (Brown et al, 2009;Nemeth and Janacsek, 2011).…”
Section: Effect Of Tacs On Gms Consolidationmentioning
confidence: 76%
“…This could indicate that motor memories are either robust, less susceptible to interference or more efficiently retrieved in our old participants (Brashers-Krug et al, 1996). Nevertheless, the improved consolidation we observed in the old group was unexpected because studies generally report either reduced (relative to young subjects) or complete absence of performance improvement during retesting of motor sequence tasks in older adults (Brown et al, 2009;King et al, 2013;Cornelis et al, 2016;Meissner et al, 2016). Late improvement (after 12 or 24-h off-line period) of GMS was also reported in elderly individuals (Brown et al, 2009;Nemeth and Janacsek, 2011).…”
Section: Effect Of Tacs On Gms Consolidationmentioning
confidence: 76%
“…Elderly participants demonstrated intact motor learning on simple tasks, such as the SAT. This is supported by intact motor learning on the random blocks of the IPLT (Cornelis et al 2016 ). These tasks were simple in that only one short, fast, straight movement was required towards a clearly visible target.…”
Section: Discussionmentioning
confidence: 91%
“…This is in contrast with the reduced performance in the CVLT, a cognitive learning task, where individuals with schizophrenia performed worse than both controls and the elderly, highlighting their cognitive difficulties. Manifestations of a cognitive deficit interfering with motor learning tasks were observed in the implicit sequence learning task, in which subjective sequence awareness arose significantly less (Cornelis et al 2016 ). Therefore, it can be suggested that individuals with schizophrenia are impaired on sensorimotor learning paradigms in which explicit cognitive processes play a role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently presented data are part of a larger study in which the same participants were tested on a large range of sensorimotor learning tasks. In a motor sequence learning task, patients with schizophrenia demonstrated a minor reduction in learning, which became apparent only after extensive training and could be attributed to a deficit in explicit learning [53]. In two other tasks investigating implicit learning, a sensorimotor speed task [54] and a rotary pursuit task [55], preserved implicit learning in schizophrenia was demonstrated.…”
Section: Discussionmentioning
confidence: 99%